The Impact of Forensic Skills on Fraud Detection in Federal Government Agencies in Nigeria - Ofili, Ugwudioha; Ebogbue, Celestine Chukwutem; Idogho, Abraham Momoh (Ilomata International Journal of Tax and Accounting, 2024)
Fraud in Nigerian federal government agencies is a persistent issue. This study explores the impact of forensic skills on fraud detection within these agencies, building upon the established connection between forensic accounting and its effectiveness in uncovering fraudulent activity. To achieve this, we investigated the impact of forensic and audit skills on fraud detection in the federal government agencies in Nigeria, identifying its implications on government resources. The focus was on all the federal government ministries and agencies in Abuja (the Federal Capital Territory). With the stratified random sampling, a sample size of 100 was selected. The non-experimental research approach was adopted in the collection and analysis of data with the Ordinary Least Square (OLS) and Regression analysis used to interpret the data. The results of the findings indicated that no significant relationship exists between forensic skills and fraud detection (where the p-value of 0.507 > 0.05 significant level), and the existence of a significant relationship between audit skills and fraud detection in federal government agencies (with a p-value of 0.000 < 0.05 level of significance). This study recommends increased investment in personnel with forensic and audit skills as a course of action to strengthen fraud detection efforts and improve financial accountability in federal government agencies in Nigeria.